Assessment of prostate cancer radiotherapy using three-dimensional treatment planning technique - Fatima Jassim Mohammad Hassan; Haydar Hamza Obaid Alabedi (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the available commercial treatment planning system using three-dimensional conformal radiation therapy with respect to treatment for prostate cancer patients. Method: This is a cross-sectional study was conducted from June 2021 to February 2022 at the Baghdad Centre for Radiation Therapy and Nuclear Medicine, Baghdad, Iraq, and comprised patients with prostate cancer who were treated with 6MV or 10MV energy using three-dimensional conformal radiation therapy technique, and irradiated using a linear accelerator. The patents were divided into three treatment phases. The prescribed dose in Phase I was 5000 centigrade, in Phase II it was 1800 centigrade, and in Phase III it was 600 centigrade. The number of beams used was 5 and 7. Data was analysed using SPSS 24. Results: Out of 35 patients, 10 (28.6%) in phase I, 15 (42.8%) in phase II, and 10 (28.6%) in phase III. The PTV dose of 5 and 7 beams 6MV energy at the centre was higher than at 1mm, 2mm, and 3mm p values = (0.351, 0.013*, 0.076, 0.295), respectively. Dose to the rectum comparing 6MV and 10MV for beams 5, and 7. The dose to the rectum on phase one at 6MV and 10MV was similar for 5 beams (p=0.611) and 7 beams (p=0.778). A significant difference was seen for 7 beams (p-value=0.008). Phase three showed significant variations in rectum dose at 6 MV and 10MV for 5 beams (p=0.0004). For bladder, a significant difference observed between the energies for 5 beams on phase one and three (p-value=<0.00001*, 0.002*), while at 7 beams only phase 3 were significant (p-value=0.041*) Conclusion: The three-dimensional conformal radiation therapy plan with 10MV energy and a higher number of beams gave a higher coverage of dose for prostate tumours and was found to be a safe dose for the rectum and bladder. Key Words: Nuclear Medicine, Rectum, Urinary Bladder, Prostatic Neoplasms, Particle Accelerators, Tumour, Radiotherapy